Comparison of ant-associated beetle communities inhabiting mounds of forest-dwelling ants in forests and forest clearings - Salla K. Härkönen; Jouni Sorvari (CANADIAN SCIENCE PUBLISHING, NRC RESEARCH PRESS, 2022)
Red wood ant (Formica rufa group) nests contain a highly diverse community of invertebrates, which is largely due to their abundant resources and regulated microclimatic conditions. Clear-felling, however, causes nest mounds to lose surface layer moisture, thus disrupting their inner stability. To study the effects of clear-felling on ant-associated beetles (myrmecophile and non-myrmecophile), 41 nests of Formica aquilonia Yarrow, 1955 located on three clear-fells and adjacent mature forest stands were sampled, and the beetle communities between these habitats were compared. We investigated how habitat type, nest surface moisture content, nest volume, and isolation affect the community composition, species richness, and abundance of beetles. Beetle community composition or species richness did not markedly differ between clearings and forests, although total abundance was higher in forests. Also, total species richness and abundance and myrmecophile abundance increased with increasing moisture content. Overall, nests with similar moisture content and volume had similar species compositions. Nest volume was negatively correlated with myrmecophile species richness. Nest isolation was not related to species richness or abundance. The lower abundances in clearings could be problematic in the long term, as small populations are more likely to become extinct. To ensure the survival of ants and their associates, small-scale clearings should be preferred.